Simulation of skiing turns with a multibody skier and a ski-snow interaction model - Oberegger, U. F.; Kaps, P.; Mössner, M.; Heinrich, D.; Nachbauer, W. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: In Alpine skiing, a skier steers his skis by actions like edging, leaning inwards, angulations, leaning forwards or backwards. We study the influence of such actions by augmenting ski-snow interaction to our skier model. The models for the skier [1] and the ski-snow interaction [2] are validated. With the skier model [1] consecutive turns could be simulated when the track of one ski is given by a spline curve. The purpose of the present work is to study the influence of the above actions for varying snow conditions characterized by the ski-snow interaction model.